Impact of Initial Environmental Conditions on Germination, Growth, and Development of Cucumis Sativus at Lamjung - Chapagain, A.; Khanal, A. (Journal of the Institute of Agriculture and Animal Science, 2018)
Cucumber is the fourth most important vegetable crop worldwide favored for its edible fruit. Cucumber cannot be grown in the winter months due to its intolerance to cold and frost. An experiment was conducted in IAAS, Lamjung to test the effectiveness of various nursery raising conditions for achieving earlier harvest in spring. Three treatments viz. cold frame, hotbed, and open were selected and replicated 30 times each. Data on germination speed, germination percentage, true leaf initiation, plant height, tendril initiation, days to first flowering, days to harvesting, length and diameter of fruit and fruit yield were recorded. Hotbed achieved earlier germination (8 days) followed by cold frames (8.57 days) and open (12.73 days) respectively with cold frame having the highest germination percentage (98%) followed by a hotbed (96%) and open (90%). True leaf initiation was earlier in a cold frame (21.5 days), followed by hot bed (22.83 days) and open (30.97 days). Transplanting of cold frame and hotbed seedlings could be performed 10 days prior to open. Final height attained was significantly maximum for cold-frame plants (97.93 cm) and minimum for a hotbed (76.19 cm) with open being indifferent (86.17 cm) to cold frame and hotbed. Days to tendril initiation, days to flowering and days to first harvest were 57.52, 66.87 and 82.93 days respectively for cold-frame which was significantly minimum compared to hotbed (64.04, 70.38 and 86.95 days) and open (65.73, 71.23, 85.58 days), both being indifferent. Significantly maximum yield was obtained from cold-frame (1465.73 g) with open yielding significantly minimum (1004.06 g) and hotbed being indifferent (1122.45 g) to cold frame and open. Cold-frames are found to be comparatively effective to hotbed and open condition with 3.12 days earlier and 35% higher yield.